SYMBOLIC CONSUMPTION DRAMATURGY: MILLENNIAL-Z SOCIAL IDENTITY CONSTRUCTION THROUGH BLOK M AFTERNOON STROLL PHENOMENON - Fathania Apvianti; Elly Malihah; Mirna Nur Alia Abdullah (UNIVERSITAS SEBELAS MARET (UNS), 2026)
The transformation of urban public spaces, particularly the afternoon stroll phenomenon in Blok M, reflects a shift in consumption patterns from utilitarian to symbolic among Millennials and Gen Z. This study analyzes impression management and social identity performativity of these generations through digital representations of symbolic consumption in Blok M on social media. Employing a qualitative approach with phenomenological methods, the research involves three informants selected based on diverse experiences related to the phenomenon. Data were collected through in-depth interviews and observations, and analyzed using Goffman's dramaturgical theory and Tajfel-Turner's social identity theory. The findings indicate that content creation is guided by deliberate strategies, such as choosing aesthetic locations, coordinating outfits, and applying visual edits. Motivations for posting range from self-documentation to performing trendiness, with implications for social identity construction. Symbolic consumption is evident in the selection of dining spots and fashion that align with social media trends. The afternoon stroll becomes a lifestyle expression, where social media serves as an extended identity stage. Ultimately, the phenomenon reflects how consumption in urban spaces transforms into performative acts, reinforcing symbolic markers of class and shaping collective youth identity in digitally mediated environments.